Consumer Purchase Decision on Chicken-Nugget Purchasing Behavior in Semarang City - Adinda, Tania; Mukson, Mukson; Prasetyo, Edy (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 3 (2021): Vol.15, No.3, 2021DO - 10.24843/SOCA.2021.v15.i03.p16, 2021)
Today, the level of processed-food consumption is significantly increasing. It is causing a high supply of this food by some business enterprises and tense competition between them. This study aimed to analyze the chicken-nugget consumer purchase decision-making, factors affected the purchase decision and the effect of those factors on the consumer purchase decision in Semarang City. This study employed a case-study method and involved 120 respondents aged ?17 years old who purchase chicken-nugget products selected by accidental sampling technique. The descriptive, factor, and multiple linear regression analyses were used to analyze the study data. Results revealed that the chicken-nugget purchase decision process consisted of some steps: need identification, finding adequate information, alternative evaluation, purchase decision, and evaluation after product purchasing. This purchase-decision was simultaneously affected by cultural, social, personal, psychological, product, price, location, and promotion factors. Cultural, personal, psychological, product, and promotion factors partially affected the consumer purchase decision.